Pengaruh tingkat pendidikan, tekanan pekerjaan dan kualitas SDM terhadap kinerja pegawai pada Dinas Pendidikan dan Kebudayaan Kabupaten Balangan - Rakhman, Deddy; Kadir, Abdul (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The purpose of the study was to determine and analyze the effect of education level, job pressure and quality of human resources simultaneously and partially on employee performance, to determine and analyze the influence between variables of education level, job pressure and quality of human resources which had a dominant influence on employee performance at the District Education and Culture Office. Balangan. This research is based on the type of data, it is an associative research with a quantitative paradigm and statistical calculations using the SPSS program, while for the population and sample, 89 people consist of ASN and Honorary employees at the Education and Culture Office of Balangan Regency. The results showed that the level of education, work pressure and the quality of human resources simultaneously significantly affect the performance of employees at the Department of Education and Culture of Balangan Regency. Education level, job pressure and quality of human resources have a significant effect partially on employee performance at the Education and Culture Office of Balangan Regency and the quality of HR has a dominant influence on employee performance at the Balangan Regency Education and Culture Office.